(untitled) (Collection of scientific works «Modern structures of metal and wood», 2020)
The modern state of the question is generalized, the tasks of researches are put, basic pre-conditions of application of defence of on-the-road steel build constructions are marked from high temperature influences. The review of results of researches of different aspects of defence of constructions is resulted, determinations of the technical state in the process of exploitation after different influences and its adjusting by repair, strengthening or replacement. Works of the known scientists in this area, in which positions of theory of calculation of building constructions are expounded taking into account high temperature influences, are analysed. The analysis of existent methods allowed to set that the methods of calculation of steel constructions, estimations of their technical state and ground of possibility of subsequent reliable exploitation of constructions of buildings and buildings, taken to the practical use absent after different influences. Procedure of planning, device and estimation of fire-resistance of steel constructions in the process of exploitation is offered. The method of research of the technical state of steel constructions, damaged as a result of fire is resulted. During implementation of works a hearth and reasons of fire, size of maximal temperature at a fire, areas of thermal damages, is set, duration of heating in the different areas of fire etc. On the basis of findings a conclusion prepares about the technical state of constructions and possibility or impossibility of proceeding in their service ability. In accordance with requirements it is recommended to determine the criteria of estimation of the technical state and fire-resistance of material and constructions a project and normative document on the whole. The method of receipt of determining parameters of the technical state and fire-resistance of steel constructions is developed and approved. It is foreseen, that constructions and elements during all of life cycle as a result of senescence, degradation and other influences can consistently be in each of four technical states. The results of estimation of the technical state and fire-resistance of constructions of the buildings, which got damage as a result of exploitation of both fire and measure on adjusting of the technical state and fire-resistance of constructions are presented.